Philanthropy Under Uncertainty: Muslim Religious Giving During the COVID-19 Pandemic (Journal of Public and Nonprofit Affairs, 2025)
This study investigates the demographic, religious, and psychological correlates of charitable giving during times of uncertainty. We employ structural equation modeling to understand the mechanisms that underlie faith-based philanthropy amongst Muslims. For this purpose, we analyzed Muslim American philanthropy during the month of Ramadan in 2020, a month traditionally associated with increased religiosity and philanthropy. Utilizing a sample of 1,722 Muslims in the United States and Canada, uncertainty intolerance was associated with financial anxiety (B = .26), which in turn was related to donating less money (B = -.06). Financial anxiety was also associated with subjective financial well-being (B =.-.22), which was associated with donations (B = .11). We also found that income (B = .23), education (B = .30), and age (B = .28) positively predicted charitable giving. Increased religious practice (B = .07), such as prayer and reading scripture, was also associated with donating more money. Our results add valuable insights to the literature about the predictors and mediators of religious giving and philanthropy under uncertainty.